Assessment of Integrating Solar Energy Technology with Combined Cycle Power Plants - Abd Elrahman, Ahmad Abd Elmahmoud Mohmed (2014)
A Master of Science thesis in Mechanical Engineering by Ahmad Abd Elmahmoud Mohmed Abd Elrahman entitled, "Assessment of Integrating Solar Energy Technology with Combined Cycle Power Plants," submitted in June 2014. Thesis advisor is Dr. Mohamed Gadalla and thesis co-advisor is Dr. Andreas Poullikkas. Soft and hard copy available.